Jejunal atresia presenting as meconium cyst with polysplenia in a newborn: an extremely rare association - ., Rashi; Basu, Kalyani Saha; Biswas, Samiran; Barman, Shibsankar (International Surgery Journal, 2019)
Jejunal atresia (JA) presenting as meconium cyst with polysplenia is an extremely rare condition. We reported a case presenting with abdominal distension and feculent vomiting. Exploration revealed a type IV JA with dilated proximal segment presented as a large cyst filled with air and meconium. Polysplenia diagnosed incidentally.